Impact of Artificial Intelligence on Academic Performance in High School Students: A Correlational Study - Cobos-Gutierrez, Carlos Eduardo (2024)
This study explored the relationship between the use of Artificial Intelligence (AI) tools and the academic performance of high school students through a correlational approach. A sample of 350 students from various socioeconomic backgrounds was analyzed to evaluate the impact of AI on key subjects such as mathematics, sciences, and humanities. The results showed a significant improvement in students' grades, especially among those who used AI tools more frequently. Additionally, access to technological devices and frequency of AI usage directly influenced academic outcomes. This study suggests that AI is an effective tool for enhancing learning, although equitable access to technology must be ensured.